Implementing a nursing systems framework in a developing country. (9th June 2017) - Cannaby, A.M.; Gkantaras, I.; Finn, A.; Foreman, B.; Butler, G.; Topping, A.; Gray, R.
Abstract : Aim: To test the effect on patient mortality of implementing a nursing systems framework across a national health system. Background: There have been five previous observational studies that have tested the effect of a nursing systems framework on clinical outcomes for patients. Implementation of a nursing systems framework in the health system of a developing country has not been evaluated. Design: Quasi‐experimental (before and after) study. Method: A nursing systems framework consisting of six themes: (i) Professionalisation; (ii) Education; (iii) Structure; (iv) Quality of nursing care; (v) An academic health system; and (vi) Communication (Professional), was implemented across the national health system of Qatar in March 2015. Routine administrative data were extracted (March 2014–February 2016) for elective admissions. Our primary and secondary outcomes were, respectively, all cause mortality at discharge and readmission to hospital (within 28 days of discharge). We split the data into two time periods: before (March 2014–February 2015) and after (March 2015–February 2016) the implementation of the nursing systems framework. Multivariable regression modelling was used to examine the effect of the framework on patient mortality, after adjusting for key confounding variables (patient age, episode acuity, intensive care admission and length of stay). Findings: Data were extracted for 318 548 patients (year 1 = 130 829; year 2 = 187 725). After adjusting for confounding, there was a significant association between the implementation of the nursing systems framework, mortality and readmission. Conclusion and implications for nursing policy and practice: Our observations suggest that the implementation of a nursing systems framework may be important in improving outcomes for patients in emerging health systems.